An analysis of institutional change in the European Union with an application to social policy - Martin Kolmar (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Institutional change is guided by rules. In the European Union these rules are given by Art. 250-252 of the Treaty of Amsterdam. These articles define the actors and rules that bring about changes in policies in the European Union. We analyze these articles as games in extensive form and characterize and compare the equilibria of these games. This analysis identifies the decisive actors the conditions under which it comes to institutional change within the European Union. In addition we analyze the tendencies for centralization inherent in these decision procedures as well as their ability to come up with solutions that are a good compromise between all actors.
Keywords: 330; endogenous institutional change; law and economics; Verfassungsreform; Institutioneller Wandel; Extensives Spiel; Politische Entscheidung; EU-Sozialpolitik; Theorie; EU-Staaten